Legislative measures to further strengthen the victims and witnesses’ legal protection in the Republic of Kazakhstan - Oleinik, V.I. (Bulletin of the Karaganda University “Law Series”, 2021)
The rights and freedoms of individuals and citizens, their honor and dignity are of great importance to society and the State. The article is dedicated to modern problems of victims and witnesses, legal protection and improvement of prosecutions in current criminal proceedings. Considering the legal status, the author defines them as key figures in the criminal process whose rights and legitimate interests have been violated due to committing a crime. It is highly demonstrated that one of the social expectations of society is the protection and restitution of violated rights. Based on the legislative activity of the Parliament of the Republic of Ka- zakhstan, the author has illustrated some certain conceptual amendments adopted by the deputies in the current criminal law and procedural legislation aimed at strengthening the adversarial and openness of the criminal process, expanding the powers of competitiveness and openness of the criminal process and empowering the defense. Particular attention is paid to one of the novelties of criminal procedural legislation regulating the legal status of a witness entitled to protection, its difference from a simple witness, the measures taken by the legislator aimed at eliminating conflicts and legal gaps in determining the procedural status of this participantin the criminal process. The article also touches on such relevant issues as ensuring the safety of persons in- volved in criminal proceedings; the right of victims to receive qualified legal assistance; compensation for moral and material damage caused by a crime to the victim; the institution of compensation for harm to victims. Based on the analysis of national and foreign legislation, the author demonstrated the effectiveness of the tools of “restorative justice” and compensation for harm from a special fund to support victims. The article explains the “legal nature” of one of the novelties in the domestic legislation “forced payment” as another measure of criminal–legal impact. A detailed analysis of the legal framework for the implementation of the new institute of compensation to victims in our country and the mechanism of the corresponding fund for providing urgent, one-time financial assistance to victims is provided.